2021
DOI: 10.1111/jsr.13337
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional case‐control study of the relationships between pharyngeal compliance and heart rate variability indices in childhood obstructive sleep apnoea

Abstract: A combination of noradrenergic and antimuscarinic agents reduces the apneahypopnea index (AHI) in adult patients with obstructive sleep apnoea (OSA) via reduced upper airway collapsibility, suggesting that a shift in the sympathovagal balance improves OSA. The objectives of our present case-control study were to assess heart rate variability (HRV) indices in the stages of sleep in children with and without OSA to evaluate OSA-induced sleep HRV modifications and to assess whether increased collapsibility measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Chaicharn (184). Autonomic activity may play a key role in pharyngeal compliance of childhood OSA (185). Another application of HRV in childhood OSA is to evaluate treatment response.…”
Section: Hrv In Pediatric Osamentioning
confidence: 99%
“…Chaicharn (184). Autonomic activity may play a key role in pharyngeal compliance of childhood OSA (185). Another application of HRV in childhood OSA is to evaluate treatment response.…”
Section: Hrv In Pediatric Osamentioning
confidence: 99%
“…Similarly, south Asian men have higher heart rates compared with European men, which may be indicative of altered sympathovagal balance (Bathula et al, 2008). Similarly, we have shown that children with increased pharyngeal compliance exhibit decreased sympathetic tone associated with increased AHI in NREM sleep, suggesting altered sympathovagal balance in OSA (Bokov et al, 2021). Thus, ethnic differences in sympathovagal balance may explain this independent effect of ethnicity.…”
Section: Discussionmentioning
confidence: 62%
“…Secondly, due to a relatively small sample size, we could not detect further cephalometric variables that may be relevant to OSA presence and severity. Also, in this study, we used OAHI ≥1 time/h as a cutoff value to determine OSA children, while some studies use different values (>1, >1.5, >2) (49,50). The different cutoff values may influence the results.…”
Section: Discussionmentioning
confidence: 99%